Β-Sitosterol increases mitochondrial electron transport by fluidizing mitochondrial membranes and enhances mitochondrial responsiveness to increasing energy demand by the induction of uncoupling in C2C12 myotubes. (May 2016) - Wong, Hoi Shan; Leong, Pou Kuan; Chen, Jihang; Leung, Hoi Yan; Chan, Wing Man; Ko, Kam Ming
Highlights: BSS stimulated mitochondrial electron transport and the associated induction of mitochondrial uncoupling. BSS enhanced the responsiveness of mitochondria to ATP production to increased energy demand. BSS may offer a promising approach to improve mitochondrial ATP production in skeletal muscle. Abstract: Mitochondrial bioenergetic adaptation is important for maintaining normal physiological functions, particularly in skeletal muscle, which displays a wide range of variations in energy demand. β-Sitosterol (BSS), an active component of Cistanches Herba, can influence mitochondrial membrane potential through its actions on mitochondrial electron transport and mitochondrial uncoupling in C2C12 myotubes. Since mitochondrial electron transport and uncoupling constitute a substrate cycle for mitochondrial ATP generation that can increase its regulatory efficiency, we postulated that BSS may enhance the responsiveness of mitochondria to ATP production to increased energy demand. Our findings indicated that BSS fluidizes mitochondrial membranes and thereby stimulates mitochondrial electron transport and induces uncoupling protein-mediated mitochondrial uncoupling in C2C12 myotubes. BSS-preincubated cells also demonstrated a more rapid mitochondrial response to ATP production upon increasing energy demand in C2C12 myotubes, wherein the increase in mitochondrial membrane fluidity and the induction of mitochondrial uncoupling were involved. Therefore, BSS may offer a promising approach for improving mitochondrial bioenergetic adaptation to energy demand in skeletal muscle, particularly during physical exercise and in patients suffering from mitochondria-related muscle dysfunction.